Design and analysis of a novel bolted composite π joint under bending load. (15th May 2016) - Zhou, Longwei; Zhang, Donghua; Zhao, Libin; Zhou, Xiaohong; Zhang, Jianyu; Liu, Fengrui
Abstract: A novel design of out-of-plane composite π joints is proposed to elevate the load carrying capability. This design adopts an in-plane π-shaped section scheme along the loading direction to eliminate the delamination damage, which commonly occurs in traditional composite π joints, and uses bolts to connect the joint and other structural components. Static experiments of the novel bolted composite π joint and an aluminum counterpart were conducted. The bolted composite π joint exhibited a larger load carrying capability with a massive weight reduction. Compared with existing static experimental results from a traditional design, the novel bolted composite π joint also showed a greater load carrying capability. A progressive damage analysis of the bolted composite π joint was further performed and validated by experimental data. Based on numerical simulation, the progressive damage process and failure mechanism of the bolted composite π joint were discussed. It follows that the novel design not only eliminated potential weaknesses in deltoid fillers but also brought positive factors of composite into play and substantially strengthened the composite π joint. Graphical abstract: Highlights: An in-plane π-shaped section scheme along the loading direction is proposed. Bolts are used in the π-shaped joint to improve the load transfer capacity. The novel composite π joint shows an improved load carrying capacity. The progressive damage process and failure mechanism are discussed.